2004
DOI: 10.1016/j.ijgo.2004.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Heterotopic pregnancy after in vitro fertilization–embryo transfer

Abstract: These cases illustrate that good perinatal outcomes can be achieved by surgical intervention in heterotopic pregnancies, even in the event of a ruptured cornu.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
8

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 22 publications
1
43
0
8
Order By: Relevance
“…In addition, the interstitial region receives a very significant blood supply from the uterine and ovarian arteries branches. An HP after salpingectomy can be as much threatening as EP, because the tubal interstitium rupture may lead to a sudden and excessive blood loss, worsened also by hypervascularity due to the intrauterine pregnancy [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the interstitial region receives a very significant blood supply from the uterine and ovarian arteries branches. An HP after salpingectomy can be as much threatening as EP, because the tubal interstitium rupture may lead to a sudden and excessive blood loss, worsened also by hypervascularity due to the intrauterine pregnancy [34].…”
Section: Discussionmentioning
confidence: 99%
“…Tubal stump pregnancies can occur when the embryo or the oocyte migrate through the uterine cavity or when the oocyte passes through a tubal fistula [35]. A review of the literature conducted by Chin et al [34] reported 22 cases of cornual pregnancies after IVF-ET.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the biggest advantage of vaginal ultrasonographic guided drug administration is that anesthesia and surgery can be avoided. However, surgical treatment has to be used in cases where there is a risk of excessive bleeding if the ectopic mass ruptures, where abnormal location makes access for drug administration difficult, or where intrauterine gestation is close [4,7]. In addition, a cornual HP should be treated to maintain a normal intra-uterine pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, approximately 50% of heterotopic pregnancies present symptoms of tubal rupture. Surgery is usually required and MTX is contraindicated (Chin et al, 2004;Fernandez et al, 2004). In cases of heterotopic pregnancy with an association of intra-uterine pregnancy and non-tubal pregnancy with embryonic cardiac activity, an alternative treatment could be local injection of KCL under ultrasound guidance.…”
Section: Heterotopic Pregnancymentioning
confidence: 99%